Measuring political legitimacy in two dimensions: internal and external measures - Harfst, Philipp; Wiesner, Claudia (Frontiers in Political Science, 2024)
Research on political legitimacy encompasses two distinct traditions, one institutionalist and another drawing on political culture accounts of legitimacy. Recent contributions argue in favor of an integration of these two vantage points in the study of political legitimacy. Following these lines of reasoning, we investigate empirically whether a two-dimensional approach in political legitimacy research integrating the institutionalist and political culture perspectives can contribute to establish a more comprehensive and nuanced view on political regimes and their legitimacy. We conceptualize political legitimacy in combining an external normative with an internal empirical perspective, collect data for both and compare the relationship between these two dimensions of political legitimacy in an internationally comparative framework. Using data from Integrated Values Surveys and Varieties of Democracy we find that both dimensions are closely linked in general, discover important deviations from this pattern in the case of citizens' performance evaluations, pinpoint a particular group of hybrid cases that either lost internal or external legitimacy while collecting positive evaluations on the other dimension, and discuss the consequences of these findings for regime stability and future research on political legitimacy.